Comparison of radiation exposure associated with transradial and transfemoral access: An updated meta‐analysis. Issue 1 (9th December 2022) - Saqib, Najam; Pir, Muhammad S.; Rajagopalan, Sharath; Patel, Tejas M.; Pancholy, Samir B.
Abstract: Objectives: To assess differences in radiation exposure between transradial access (TRA) and transfemoral access (TFA) for coronary procedures. Background: TRA is associated with increased radiation exposure as compared to TFA. We compared radiation exposure between the two access sites. Methods: Databases were searched from June 2014 to August 2021 for randomized controlled trials (RCTs) reporting coprimary outcomes of fluoroscopy time (FT) and/or dose area product (DAP) comparing TRA with TFA. Meta‐regression was performed to assess the behavior of weighted mean difference (WMD) in FT from 1995 to 2021. Observational study data was used for corroborative evidence. Results: Data from 8 RCTs (11, 611 patients) showed the WMD of FT was 0.62 min (37 s) (95% confidence interval [CI]: [0.08−1.17], p = 0.023) in favor of TFA, WMD in DAP (9169 patients) was 1.94 Gy.cm 2 (95% CI: [−2.1 to 5.9], p = 0.35) showing no significant difference. Pooled data from OBS and RCTs (83, 990 patients) showed a similar trend. Studies from outside US between 1995 and 2021 showed WMD of FT between TRA and TFA of 0.88 min (52 s) (95% CI: [0.67−1.09], p = 0.005) versus 2.1 min (126 s) (95% CI: [1.38−2.8], p = 0.005) for US in favor of TFA. Meta‐regression showed a declining WMD of FT between TRA and TFA from 1.6 min (96 s) in 1996 to 0.5 min (30 s) in 2020 with the lower limit of CI crossing the zero line in 2019. Conclusion: Radiation exposure between TRA and TFA continues to decrease overtime and is becoming clinically nonsignificant.